Analisis Partisipasi Keluarga Pada Program Perbaikan Gizi Balita Melalui Aplikasi Mobile - Nur Rosida Aisiana (Jurusan Kebidanan Politeknik Kesehatan Kemenkes Surabaya, 2022)
Introduction. The nutritional status of children aged 0-23 months is an important priority to increase the growth and development of children. Nutritional problems in Indonesia are still quite high. Family participation has an important role for optimalization nutrition programs for children. However, involving parents in the program is still a challenge. Use of mobile applications provides the potential for better health services. The purpose of this literature review is to conduct a systematic review of several recent research results using a quasi-experimental design and a randomized controlled trial that examines family participation in nutrition improvement programs through a mobile application for various cases. Methode. This type of research is Literature Review with a research design using the Preferred Reporting Items for Systematic Review, Meta Analysis (PRISMA) and Population, Intervention, Comparation, Outcomes, Study design (PICOS) approach as well as selection and quality assessment using the Joanna Briggs Institute Checklist (JBI Checklits). Article searches were carried out in four electronic databases within the last 5 years published in both Indonesian and English. There were 1.344 articles found, then the selection was carried out, leaving 18 articles that suitable the criteria. Result. Of the 18 articles reviewed, 11 articles found the effect of mobile applications on increasing family knowledge, 4 articles found the effect of mobile applications on increasing participation and 3 articles found the effect of mobile applications on improving children's nutritional status. Discussion. Mobile applications have a significant effect on increasing parental knowledge and participation in improving children's nutrition, but not significantly on improving children's nutrition. There are many factors in the study that can affect the result Keywords: Mobile application, knowledge, participation, nutritional status